Promoting Employee Mental Health and Well-being in the Workplace: The Role of Human Resource in Creating a Healthy Work Environment - Ahmad, Ahmad (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The mental health and well-being of employees in the workplace is an important aspect of creating a healthy work environment. The Human Resources (HR) department has a key role in promoting a positive work culture that supports employee mental health. This research aims to investigate how HR policies and practices can improve employee mental well-being. Using the Systematic Literature Review method, this research identifies effective HR strategies in supporting mental health in the workplace. The research results show that work flexibility and leadership support have a positive impact on employee well-being. The practical implications of this research include the importance of implementing flexible work policies and mental health programs to increase job satisfaction and organizational productivity.